The Collaboration of Question and Answer Technique and See Differences Game in Improving Studentsâ English Speaking Ability at Grade Four Cigugur State Elementary School - Sari, Agatha Kristi Pramudika; Falah, Irfan Fajrul (UICELL, 2017)
This study aims to figure out the implementation of question and answer technique that collaborated with see differences game in improving studentsâ speaking ability which conducted on grade IV of Cigugur State Elementary School of Kuningan. The research method used is Quasi-Experimental Design with Non-Equivalent Control Group PretestPosttest Design. The technique of collecting data are through observation and test. The results shown in this research are 1) the observation resulted in the average of 85.75%, it means the learning process by applying the collaboration of question and answer technique and see differences game have been done very well. 2) Independent Samples Test in experimental class resulted by Sig. (2-tailed) = 0,000 <Î± = 0.05, it means there is the influence of question and answer technique and see differences game in improving studentsâ speaking. The data is supported by N-Gain test that shows a difference in the level of 1 percent (t = -5,166; p <0.01), it means there is a significant increase in students speaking ability after question and answer technique and see differences game is implemented. So the treatment given to the experimental group was successful.